Paulo Freire´s research itinerary in studies developed in postgraduate Health programs (Brazilian Journal of Health Research, 2021)
Introduction: The health field has been using the teaching approach by Paulo Freire, which, based on participatory methodology, enables group experience, with emphasis on dialogue, and contributes to emancipatory health education. Objective: Identifying the production profile of research carried out in dissertations and theses that used carried out based on Paulo Freire’s Research Itinerary in postgraduate health programs in Southern Brazil. Method: Qualitative bibliographic research. Inclusion criteria comprised, dissertations and theses produced in the health field, based on stages such as Thematic Investigation, Coding, and Decoding, and Critical Unveiling of Research Itinerary, published from 2008 to 2017, in full version and available online at website of Federal Universities in Southern Brazil. Data collected from the studies were organized in a structured instrument and subjected to content analysis. Results: It was clear that academic studies were carried out based on this method. However, of the 57 identified studies, only ten used Paulo Freire’s Research Itinerary and took into consideration all three stages of the method. Conclusion: It is noteworthy that the Research Itinerary stages remain poorly known by researchers, who cannot fully use the method to carry out scientific investigations.
Keywords: Methods; Nursing; Research; Community-Based Participatory Research; Qualitative Research